Analysis and interpretation of difficult samples—The interaction of a DNA quantification kit with the right STR assay may facilitate processing of critical trace material. (December 2015) - Di Pasquale, F.; Cornelius, S.; König, M.; Scherer, M.; Prochnow, A.; Peist, R.
Abstract: Challenging samples were processed using alternative quantification and STR PCR methods that include internal performance controls. These internal controls can be used to monitor potential inhibition or degradation of a sample. We compared the different workflows with regard to the predictive value the internal controls provided.